Symbol as a meeting space between material and transcendental orders in José Ángel Valente’s poetry (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
As José Ángel Valente himself used to say, his poetry emerged from a matriarchal universe, a place dominated by water and earth. This sensitive world will be considered opposite to the transcendental object pursued towards the end of his last creative phase. The increasingly abstraction achieved in this phase will pose a well-known language problem: the word will be on the edge of the nothingness. Between these two extremes, a universe full of symbols will be created by connecting elements of the poet’s universe. All of these symbols, in their perfect way, will express the full unity between the material and spiritual aspects of Valente’s poetry.
Keywords: Poetry; José Ángel Valente; symbol; imaginary universe